Influence of impeller and guide vane hub size on hydraulic performance of mixed-flow pump. Issue 3 (March 2019) - Zhang, Wenpeng; Tang, Fangping; Zhou, Sheng-ying; Shi, Lijian; Xia, Ye
Abstract: Because of the beneficial properties of the mixed flow pump, it is widely used in the fields of irrigation and drainage. Our research team designed a mixed-flow pump, which with maximum efficiency more than 87%. However, its maximum operating efficiency range is biased towards large flow areas. In order to find the reasons for deviation from the design head, we have a three-dimensional modeling of the pump system and numerical simulation to analyze the internal flow. The numerical simulation results agree well with the experimental results and the experimental results verified the accuracy of the numerical simulation. When Q = 288 L/s, 360 L/s and 432 L/s, poor flow conditions appear near the hub. We refer to change the impeller and guide vane hub ratio method which only change the impeller and guide vane hub radius as blade shape remains unchanged. The result of this approach shows that it is possible to shift the highest efficiency point to the design point, but this can result in poor impeller performance. So we try to only change the guide vane hub radius and numerical simulation results show that it is effective. Finally, in the design head point, experimental test proved that when the guide vane hub radius is increased by 11 mm, pump system efficiency is increased by about 2.3%. This article can provide some references for the design of a mixed-flow pump.